2019
DOI: 10.1038/s41598-019-42847-x
|View full text |Cite
|
Sign up to set email alerts
|

GM1 Ganglioside Modifies α-Synuclein Toxicity and is Neuroprotective in a Rat α-Synuclein Model of Parkinson’s Disease

Abstract: While GM1 may interact with α-synuclein in vitro to inhibit aggregation, the ability of GM1 to protect against α-synuclein toxicity in vivo has not been investigated. We used targeted adeno-associated viral vector (AAV) overexpression of human mutant α-synuclein (A53T) in the rat substantia nigra (SN) to produce degeneration of SN dopamine neurons, loss of striatal dopamine levels, and behavioral impairment. Some animals received daily GM1 ganglioside administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 44 publications
5
41
0
Order By: Relevance
“…It has been hypothesized that the reduced level of plasma membrane GM1 in Parkinon's neurons can trigger the neurodegenerative process by a failure in neurotrophic signaling (e.g., BDNF/GDNF/NGF) together with a reduction of clearance promoting the α-synuclein accumulation [7,9,104,106,129,130]. Along with this, recent studies strongly demonstrated the specific binding of tetrameric α-synuclein to GM1 which promotes its α-helical conformation against the beta-sheet-rich state of α-synuclein that has been associated with its pathological aggregation in Parkinson's disease [132][133][134]. Additionally, Schneider recently reported that GM1 modifies the alpha-synuclein toxicity and is neuroprotective in a rat α -synuclein model of Parkinson's disease reducing the size of α -synuclein positive aggregates [123].…”
Section: Gm1 and Parkinson's Diseasementioning
confidence: 99%
“…It has been hypothesized that the reduced level of plasma membrane GM1 in Parkinon's neurons can trigger the neurodegenerative process by a failure in neurotrophic signaling (e.g., BDNF/GDNF/NGF) together with a reduction of clearance promoting the α-synuclein accumulation [7,9,104,106,129,130]. Along with this, recent studies strongly demonstrated the specific binding of tetrameric α-synuclein to GM1 which promotes its α-helical conformation against the beta-sheet-rich state of α-synuclein that has been associated with its pathological aggregation in Parkinson's disease [132][133][134]. Additionally, Schneider recently reported that GM1 modifies the alpha-synuclein toxicity and is neuroprotective in a rat α -synuclein model of Parkinson's disease reducing the size of α -synuclein positive aggregates [123].…”
Section: Gm1 and Parkinson's Diseasementioning
confidence: 99%
“…It was found that all major brain gangliosides were significantly decreased in male PD patients compared to healthy controls ( Seyfried et al, 2018 ). Pilot studies further showed that treating PD Patients with GM1 ganglioside could provide a disease modifying therapy and that GM1 administration reduced the size of α-syn aggregates in a rodent AAV-α-syn overexpression model ( Schneider et al, 2013 , 2015 , 2019 ). However, research of human brain lipidomics of different brain areas or cell types during aging in health and disease is limited.…”
Section: Lipid Binding Modulates Initial α-Synuclein Aggregationmentioning
confidence: 99%
“…In neurodegenerative diseases such as Parkinson's and Alzheimer's diseases, despite the great preclinical successes [18,19,[68][69][70][71], GM1 did not reach a sufficient amount in the brain target site to perform its reparative functions. Probably the reason is that these clinical trials included peripheral administration of the ganglioside, which inefficiently permeates through the BBB.…”
Section: Discussionmentioning
confidence: 99%